Gestión de la calidad y su relación con la satisfacción del usuario que acude a un hospital básico. Arenillas - El Oro 2025 - Ramírez Lalangui, Glenda Zulay (My University, 2025)
Quality in the healthcare context has evolved from a first approach, initially focused on the healthcare personnel/user relationship and encompasses the relationship with systems and services. Objective: To determine the relationship between quality management and user satisfaction in a basic hospital, Arenillas, El Oro 2025. Materials and Methods: This study was carried out under a quantitative, descriptive and correlational approach, cross-sectional, and used the SERVQUAL questionnaire along with a satisfaction questionnaire to collect data from a sample of 302 users of a Basic Hospital in Arenillas 2025. Results: The relationship between the quality of care and external user satisfaction of the Arenillas Basic Hospital, using Spearman's Rho coefficient, was -0.151 with a significance level of 0.008. Conclusion: There is a weak but statistically significant negative correlation between both variables. This suggests in this specific context, a higher perception of the quality of care does not necessarily correspond to a higher level of user satisfaction, or vice versa. In other words, as one variable increases, the other tends to decrease slightly, which raises important questions about quality management in health services.
La calidad en el contexto sanitario ha evolucionado desde un primer enfoque, inicialmente se centra en la relación personal de salud/usuario y engloba la relación con los sistemas y servicios. Objetivo: determinar la relación entre gestión de calidad y satisfacción al usuario en un hospital básico, Arenillas, El Oro 2025. Materiales y Métodos: Este estudio se efectuó bajo un enfoque cuantitativo, descriptivo y correlacional, de corte transversal, y se empleó el cuestionario SERVQUAL junto con un cuestionario de satisfacción para recolectar datos de una muestra de 302 usuarios de un hospital Básico de Arenillas 2025. Resultados: La relación entre la calidad de atención y satisfacción del usuario externo del Hospital básico Arenillas, mediante el coeficiente Rho de Spearman fue de –0,151 con un nivel de significancia de 0,008. Conclusión: Existe una correlación negativa débil pero estadísticamente significativa entre ambas variables. Esto sugiere en este contexto específico, a mayor percepción de la calidad de atención no necesariamente corresponde un mayor nivel de satisfacción del usuario, o viceversa. En otras palabras, a medida que una de las variables aumenta, la otra tiende a disminuir ligeramente, lo que plantea relevantes reflexiones sobre la gestión de la calidad en servicios de salud